Generasi Muda Kok Takut Bersuara? - Hesti Lestari; Masduki Asbari; Deftia Eka Pratiwi; Erfani Fankhiyatun Munawaroh (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to encourage young people to no longer be afraid and hesitant to express their opinions. In this study report, descriptive qualitative methods are used took notes because the data source was obtained by listening to the oral narrative from Mata Najwa's YouTube channel entitled